Characterization of Two Satellite DNA Families in the Genome of the Oomycete Plant Pathogen Phytophthora parasitica - Panabières, Franck; Rancurel, Corinne; da Rocha, Martine; Kuhn, Marie-Line (Frontiers in Genetics, 2020)
Satellite DNA is a class of repetitive sequences that are organized in long arrays of tandemly repeated units in most eukaryotes. Long time considered as selfish DNA, satellite sequences are now proposed to contribute to genome integrity. Despite their potential impact on the architecture and evolution of the genome, satellite DNAs have not been investigated in oomycetes, due to the paucity of genomic data and the difficulty to assemble highly conserved satellite arrays. Yet, gaining knowledge on the structure and evolution of genomes of oomycete pathogens is crucial to understand the mechanisms underlying adaptation to their environment and to propose efficient disease control strategies.A de novo assembly of the genome of Phytophthora parasitica, an important oomycete plant pathogen, led to the identification of several families of tandemly repeated sequences varying in size, copy number and sequence conservation. Among them, two abundant families, designed as PpSat1 and PpSat2, displayed typical features of satellite DNA, and were collectively designed as PpSat.These two satellite families differ by their length, sequence, organization, genomic environment and evolutionary dynamics. PpSat1, but not PpSat2, presented homologs among oomycetes.Characterization of transcripts of PpSat families, and the discovery of homologs in other oomycete species suggested that these satellite DNA families likely play a role in epigenetic processes. ThisThis is a provisional file, not the final typeset article reinforces the hypothesis of a conserved role of satellite candidates within this important group of pathogens.